2022
DOI: 10.3390/su141710955
|View full text |Cite
|
Sign up to set email alerts
|

Policy Cognition, Household Income and Farmers’ Satisfaction: Evidence from a Wetland Ecological Compensation Project in the Poyang Lake Area at the Micro Level

Abstract: The paper follows a field survey of 773 rural households in 14 towns in five prefectures (cities and districts) around the Poyang Lake, and uses a multivariate ordered logistic model to explore the factors influencing satisfaction with wetland ecological compensation policies (WECPs) from the perspective of rural households’ subjective cognition of WECPs and income factors. The research shows the following. (1) the overall score for satisfaction of farmers with WECPs is 3.56, which indicates satisfaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Compared with existing research, this study has drawn some novel conclusions. Pang et al (2022) found that education level influences overall satisfaction, a conclusion further corroborated in this study. However, while their research suggests gender has no significant impact and family income affects satisfaction, this study identifies gender as a significant factor affecting satisfaction and finds no significant impact of family income.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Compared with existing research, this study has drawn some novel conclusions. Pang et al (2022) found that education level influences overall satisfaction, a conclusion further corroborated in this study. However, while their research suggests gender has no significant impact and family income affects satisfaction, this study identifies gender as a significant factor affecting satisfaction and finds no significant impact of family income.…”
Section: Discussionsupporting
confidence: 89%
“…The research focuses on exploring various factors influencing the satisfaction of farmers with compensation for wildlife incidents. Previous studies on ecological compensation satisfaction have indicated that the level of understanding of compensation policies, satisfaction with compensation amounts, and policy implementation efficiency are important factors influencing satisfaction (Pang et al, 2022;Tan et al, 2020). Pang et al (2022) studied the satisfaction of farmers with ecological compensation in the Poyang Lake Wetland in Jiangxi Province, China, and found that farmers' subjective perceptions, income factors, and family labor structure significantly influence satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the previous evaluations struggled to objectively quantify residents' satisfaction. Furthermore, there remains a limited understanding of spatial variations in residents' satisfaction and their causes [14,21,22]. The supply-demand relationship between the population capacity of wetlands and the total population of communities provides a means to objectively reflect residents' satisfaction with wetland leisure demand [16].…”
Section: Introductionmentioning
confidence: 99%